Personality Traits and Job Satisfaction among Provincial Paid Teachers in Borongan City Division: Input to Personality Development Intervention - Angela S Adlawan; Flor Janine A. Glino (Future Science / FSH-PH Publications, 2026)
This study determined the provincial paid teachers’ personality traits and job satisfaction for the purpose of utilizing research results in policy and intervention development. The study employed a quantitative approach, gathering information from purposive sampling of 36 provincial paid teacher in Borongan City Division through Big Five Personality Traits and teacher job satisfaction questionnaire survey method. Mean score was used to describe personality traits and level of job satisfaction, likewise the Spearman’s Rho determine correlational analysis on significant relationship exists between specific personality traits and job satisfaction. The findings show on respondents’ personality traits in terms of openness, extroversion, and neuroticism got a mean score 3.40, 3.29, and 2.90 with moderate level, respectively. While, conscientiousness and agreeableness got a mean score 3.60 with high level of personality traits of the respondents. The level of job satisfaction got a high level with 3.81 mean score. Moreover, it was found that conscientiousness has a very strong positive relationship with teacher job satisfaction, while, agreeableness and extroversion were both found to have strong positive correlation with teacher job satisfaction. Therefore, reject the null hypothesis that stated that there is no significant relationship between job satisfaction and personality traits of respondents, specifically: agreeableness, conscientiousness, extroversion, openness, and neuroticism. The results show how crucial the provincial paid teachers to continually develop and encouraged their traits that reflect conscientiousness such as thoughtfulness, good impulse control, and display strong goal-directed behaviors.